Explicit solutions of nonlocal reverse-time Hirota-Maxwell-Bloch system - Zh. Myrzakulova; Z. Zakariyeva; K. Suleimenov; U. Uralbekova; K. Yesmakhanova (AIMS Mathematics)
In this paper, we investigate the nonlocal reverse-time Hirota-Maxwell-Bloch system, focusing on its soliton solutions using the Darboux transformation method. By deriving the Darboux transformation for this system, we obtained explicit expressions for the new potentials $ q', p' $, and $ η' $ in both the defocusing ($ κ = 1 $) and focusing ($ κ = -1 $) cases. Our analysis reveals significant differences in soliton behavior depending on the value of $ κ $, with the defocusing case producing wide, smooth solitons and the focusing case yielding narrow, highly localized solitons. These results provide a deeper understanding of soliton dynamics in nonlocal integrable systems and lay the groundwork for future studies on the influence of nonlocality in integrable models.